The Physiology of Healing Wounds (International Journal of Food and Nutritional Sciences, 2022)
A complex biological process called wound healing leads to the recovery of tissue integrity. Haemostasis, inflammation, proliferation, and tissue remodelling are the four main physiological processes that it goes through. This page explains the extracellular signalling systems that regulate wound healing as well as the biological underpinnings of it. In-depth consideration is given to the role of platelets, neutrophils, macrophages, and fibroblasts. The idea of healing by primary and secondary intention is examined. Malnutrition, hypoxia, immunosuppression, chronic illness, and surgery are just a few of the conditions that have been shown to negatively affect healing. In order to reduce patient morbidity from delayed healing, surgeons must have a thorough understanding of the fundamental physiological mechanisms involved in healing.